64Cu-chelated InP/ZnSe/ZnS QDs as PET/fluorescence dual-modal probe for tumor imaging - Ziyu Zhao; Ayaka Otsuka; Noriko Nakamura; Toshifumi Tatsumi; Kazuhiro Nakatsui; Taiki Tsuzukiishi; Tomo Sakanoue; Kenji Shimazoe; Seiichi Ohta (Science and Technology of Advanced Materials)
Positron Emission Tomography (PET)/fluorescence dual-modal imaging combines deep penetration and high resolution, making it a promising approach for tumor diagnostics. Semiconductor nanocrystals, known as quantum dots (QDs), have garnered significant attention for fluorescence imaging owing to their tunable emission wavelength, high quantum yield, and excellent photostability. Among these QDs, heavy metal-free InP-based QDs have emerged as a promising candidate, addressing concerns regarding heavy metal-related toxicity. However, to the best of our knowledge, PET/fluorescence dual-modal imaging of InP QDs has yet to be explored. Here, we developed a novel PET/fluorescence imaging probe based on radioisotope (RI) -chelated InP/ZnSe/ZnS QDs for tumor imaging. The surface of the InP/ZnSe/ZnS QDs was functionalized with polyethylene glycol terminated with either a methoxy group or a 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) chelator group. Subsequently, the RI 64Cu was chelated with DOTA on the surface of the InP/ZnSe/ZnS QDs, integrating their bright fluorescence with radioactivity. Using the obtained 64Cu-chelated InP/ZnSe/ZnS QDs, PET/fluorescence dual-modal imaging of tumor-bearing mice was conducted, demonstrating successful multi-scale imaging from the whole body to the subcellular level. This novel PET/fluorescence dual-modal probe is expected to contribute to more precise tumor diagnosis.